A Koshihikari X Oryza rufipogon Introgression Line with a High Capacity to Take up Nitrogen to Maintain Growth and Panicle Development under Low Nitrogen Conditions. (5th July 2022) - Adu, Bright G; Argete, Aizelle Y S; Egawa, Sakiko; Nagano, Atsushi J; Shimizu, Akifumi; Ohmori, Yoshihiro; Fujiwara, Toru
Abstract: Nitrogen (N) is an important macronutrient for plant growth and development. Currently, N fertilizers are required for the efficient production of modern crops such as rice due to their limited capacity to take up N when present at low concentrations. Wild rice represents a useful genetic resource for improving crop responses to low nutrient stress. Here, we describe the isolation and characterization of an introgression line, KRIL37, that carries a small region of the Oryza rufipogon genome in the Oryza sativa L. cv Koshihikari (KH) background. This line was found to grow better under low N conditions and have similar or lower C/N ratios in aerial portions compared to those in the parental KH cultivar, suggesting that KRIL37 has a higher capacity to take up and assimilate N when present at low concentrations. KRIL37 performance in the field was also better than that of KH cultivated without N and fertilizer (−F). Transcriptome analyses of 3-week-old seedlings based on RNA-sequencing revealed that KH induced a wider suite of genes than the tolerant line KRIL37 in response to low N conditions. Some ammonium transporters and N assimilation genes were found to be induced under low N in KRIL37, but not in KH. Our findings suggest that the superior growth performance of KRIL37 under limited N conditions could be due to the expression of wild alleles influencing N uptake and assimilation. Our study demonstrates the potential to use wild rice genomes to improve modern crops for low nutrient tolerance.